A comprehensive analysis of regional grain production characteristics in China from the scale and efficiency perspectives. (1st March 2019) - Yu, X.; Sun, J.X.; Sun, S.K.; Yang, F.; Lu, Y.J.; Wang, Y.B.; Wu, F.J.; Liu, P.
Abstract: Grain production in China is faced with problems including unbalanced regional distribution, mismatch of water and cultivated land resources, and low water use efficiency. Analysis of the characteristics of regional grain production can provide reference information for the optimization of grain planting layout in the region, improving resource utilization efficiency, and ensuring food security. This study aims to generate a comprehensive analysis of grain production characteristics from 1997 to 2014 in China from the perspectives of scale and efficiency. The spatial autocorrelation method was used to analyze the regional grain production pattern and the spatial differentiation characteristics in three areas (main producing areas, main selling areas and balanced areas), and path analysis was used to evaluate the main factors affecting the degree of regional comparative advantage of grain production. The results show that the main grain producing areas had the scale advantages of grain production; the scale advantages of balanced areas first increased and then decreased during the study period, while the scale advantages of main selling areas continued to decline. Grain production in the main producing areas had an obvious efficiency advantage; the balanced areas were always at a disadvantage in terms of production efficiency; the grain selling areas maintained the efficiency advantage of grain production for a long time, but the degree of efficiency advantage considerably decreased. The main producing areas had a long-term advantage of water use efficiency, while the balanced areas and main selling areas were always at a disadvantage. The areas with comprehensive advantages of grain production tended to be located in Northeast and North China. The results of path analysis show that the scale advantage was mainly affected by the level of regional development and per capita sown area of crops; the efficiency advantage and water use efficiency of grain production were positively correlated with agricultural inputs. This study provides new indices and methods for systematically evaluating the characteristics of grain production, and provides references for the optimization of grain planting and the improvement of grain production efficiency. Highlights: The paper evaluated regional grain production characteristics of China. Spatial autocorrelation and path analysis methods were used to analyze the characteristics. Comparative advantages of scale, efficiency and water productivity were assessed. Areas with high comprehensive advantage have a trend toward Northeast and North China. Region with high level of economy development has a small scale of grain production.